"They're trying to bribe you and taking away your freedoms": COVID-19 vaccine hesitancy in communities with traditionally low vaccination rates. Issue 50 (28th November 2022) - Capurro, Gabriela; Maier, Ryan; Tustin, Jordan; Jardine, Cindy G.; Michelle Driedger, S.
Abstract: Vaccination is an essential public health intervention to control the COVID-19 pandemic. A minority of Canadians, however, remain hesitant about COVID-19 vaccines, while others outright refuse them. We conducted focus groups to gauge perceptions and attitudes towards COVID-19 vaccines in people who live in a region with historically low rates of childhood vaccination. Participants discussed their perception of COVID-19 vaccines and their intention to get vaccinated, and the low rate of COVID-19 vaccine uptake in Manitoba's Southern Health Region compared to other regions in Canada. We identified three drivers of vaccine hesitancy: (1) risk perceptions about COVID-19 and the vaccines developed to protect against it, (2) religious and conservative views; and (3) distrust in government and science. Participant proposed recommendations for improving communication and uptake of the COVID-19 vaccines included: public health messages emphasising the benefits of vaccination; addressing the community's specific concerns and dispelling misinformation; highlighting vaccine safety; and emphasising vaccination as a desirable behaviour from a religious perspective. Understanding the specific anxieties elicited by COVID-19 vaccines in areas with low childhood immunization rates can inform risk communication strategies tailored to increase vaccination in these specific regions. This study adds important information on potential reasons for vaccine hesitancy in areas with historically low rates of childhood vaccination, and provides important lessons learned for future emergencies in terms of vaccine hesitancy drivers and effective risk communication to increase vaccine uptake.